Characterization of acidic lysine acylations in mycobacteria - Ye, Tong; Wang, Danfeng; Sun, Yewen; Xie, Shuyu; Liu, Tianqi; Tian, Nana; Tan, Minjia; Xu, Jun-Yu (Frontiers in Microbiology, 2024)
IntroductionProtein acetylation is an extensively investigated post-translational modification (PTM). In addition to lysine acetylation, three new types of lysine acylations characterized by the presence of an acidic carboxylic group have been recently identified and validated. These included lysine malonylation (Kmal), lysine succinylation (Ksucc) and lysine glutarylation (Kglu). Pathogens belonging to the genus Mycobacterium elicit severe diseases in mammalian hosts through the modulation of energy metabolism pathways. Throughout this process, malonyl-CoA, succinyl-CoA and glutaryl-CoA are important intermediates in metabolic pathways, including the tricarboxylic acid (TCA) cycle, amino acid and lipid metabolism. These short-chain acyl-CoAs serve as substrates for corresponding acidic lysine acylation reactions. However, the landscape of these acyl-CoAs dependent acidic lysine acylomes remains unclear.MethodsWe used the high-affinity antibody enrichment combined with high-resolution LC-MS/MS analysis to systematically investigate the global proteomic characteristics of the three acidic lysine acylations in Mycobacterium smegmatis. Subsequently, we employed in vitro enzymatic assays to validate the functional impact of acylated substrates, adenylate kinase and proteasome-associated ATPase. Furthermore, we investigated the effects of overexpressing these two substrates on the in vitro growth of Mycobacterium smegmatis, its invasion of THP-1 cells, and the influence on inflammatory cytokines.ResultsWe systematically investigated the global substrate characterization of 1,703 lysine malonylated sites, 5,320 lysine succinylated sites and 269 lysine glutarylated sites in the non-pathogenic model strain Mycobacterium smegmatis. Bioinformatics analysis demonstrated a correlation between these acidic lysine acylations and the functional roles of ribosomes, in addition to their roles in various metabolic pathways. Furthermore, we investigated the impact of lysine acylations on the functional activity of adenylate kinase and proteasome-associated ATPase, as well as their roles in mycobacterial infection process.DiscussionCollectively, our study provided an important resource on substrate characterization and functional regulation of acidic lysine acylations in Mycobacterium smegmatis, giving valuable insights into their interrelation with the biology of infectious process.